The Profile of Ciprofloxacin-Resistant Bacteria in the Rectum of Patients Undergoing Transrectal Ultrasound-Guided Prostate Biopsy, Its Relation to Post-Biopsy Infection and Alternative Prophylactic Antibiotics - Tonny Loho; Agus Rizal A. H. Hamid; Rainy Umbas; Na'imatul Mahanani (National Cancer Center - Dharmais Cancer Hospital, 2020)
Background: Fluoroquinolone has been routinely given as a prophylactic antibiotic to patients undergoing transrectal ultrasound (TRUS)-guided prostate biopsy. Currently, there is no data on the profile of fluoroquinolone-resistant bacteria, its association with post-biopsy sepsis, and alternative prophylactic antibiotics.Methods: A cross-sectional study was conducted in patients undergoing TRUS-guided prostate biopsy at Urology Clinic, Cipto Mangunkusumo National Central General Hospital between August and December 2015. Specimens were taken from rectal swabs prior to biopsy. Gramnegative bacilli and Gram-positive cocci were characterized on the Vitek®2 using GN and GP cards (BioMérieux, USA). Antimicrobial susceptibility testing was done by Kirby Bauer disc diffusion method. Post-biopsy infection was monitored within one week after biopsy by telephone call and diagnosed by clinical examination.Results: A total of 52 patients aged 52-80 years were enrolled. Sixty-six isolates grew from 52 swabs; 14 swabs among them grew 2 isolates. The commonest pathogen was Escherichia coli (78.8%), followed by Klebsiella pneumoniae (13.6%), Enterococcus faecium (3.0%), Acinetobacter haemolyticus, Morganella morganii subsp. morganii, and Enterococcus faecalis (1.5%), respectively. Ciprofloxacin-resistant bacteria were found in 33 (50.0%) isolates which were predominated by E. coli. Meanwhile, 90.4% and 96.2% of isolates were sensitive to amoxicillinclavulanate and ampicillin-sulbactam, respectively. Post-biopsy infection was established in 7 patients requiring no hospitalization.Conclusions: The proportion of ciprofloxacin-resistant bacteria in the rectum among patients undergoing prostate biopsy was 50.0%. Escherichia coli is the commonest resistant pathogen to fluoroquinolone. The recommended alternatives for prophylactic antibiotics are amoxicillinclavulanate and ampicillin-sulbactam. Routine pre-biopsy rectal swab cultures should also be encouraged.